On Uncertainty - Taylor, Jane (Kronos: Southern African Histories, 2020)
There is some uncertainty written into the form of this paper because, while it seeks to use scholarly procedures in engaging with the philosophical questions provoked by Ludwig Wittgenstein’s late speculative essay On Certainty,1 it arose out of my research toward a theatrical interpretation of that work. The article is an attempt to stage the mode of thought, as well as the state of mind, of this most complex thinker in his last years. My thoughts pay particular attention to philosophical traditions, while considering dramatic forms, spatial meanings, constellations of persons, histories, ideas, events, and designs. Moreover, I am locating the text in the context of the workshop, ‘Missing and Missed: The Subject, Politics and Memorialisation of South Africa’s Colonial and Apartheid Dead’ at which it was presented in early 2018. The workshop generated papers and conversations enquiring into the grief, abjection, rage, and discouragement that have marked so much of the violent histories of the twentieth and twenty- first centuries, and their legacies of colonialism, genocide, and geographic dislocation. The anguish of these materials requires a certain gravitas, and there might seem some waywardness in my exploring the arcane philosophical thought of a young man born into staggering wealth and privilege in Europe at the end of the nineteenth century. Nonetheless, it seems to me that Wittgenstein made a compelling and genuinely traumatised attempt to use intellectual means to come to terms with the precariousness and uncertainty of life in the twentieth century.